Phylomitogenomics of two Neotropical species of long-legged crickets Endecous Saussure, 1878 (Orthoptera: Phalangopsidae) - Anelise Fernandes e Silva; Henrique da Rocha Moreira Antoniolli; Edison Zefa; Vera Lúcia da Silva Valente; Maríndia Deprá (Genetics and Molecular Biology, 2024)
Abstract Mitochondrial genomes have provided significant insights into the evolution of several insects. A typical mitogenome contains 37 genes, and variations in gene order can indicate evolutionary relationships between species. In this study, we have assembled the first complete mitogenomes of Endecous chape and E. onthophagus and analyzed the phylogenetic implications for the Gryllidea infraorder. We performed DNA extractions and genome sequencing for both Endecous species. Subsequently, we searched for raw data in the Sequence Read Archive (SRA) in NCBI. Using the SRA data, we assembled the partial mitogenome of Dianemobius nigrofasciatus and annotated the protein-coding genes (PCGs) for nine species. Phylogenomic relationships were reconstructed using Maximum Likelihood (ML) and Bayesian Inference (BI), utilizing the PCGs from 49 Gryllidea species. The mitogenome lengths of E. chape and E. onthophagus are 16,266 bp and 16,023 bp, respectively, while D. nigrofasciatus has a length of 15,359 bp. Our results indicate that species within the infraorder exhibit four types of gene order arrangements that align with their phylogenetic relationships. Both phylogenomic trees displayed strong support, and the ML corroborated with the literature. Gryllidea species have significantly contributed to various fields, and studying their mitogenomes can provide valuable insights into this infraorder evolution.